Lactic acid and its applications / Noorlis Ahmad, Hafizah Kassim and Mohd Noor Ramlan - Ahmad, Noorlis; Kassim, Hafizah; Ramlan, Mohd Noor (2006)
For centuries, L (+) lactic acid has been a natural ingredients in a wide range of products. Long before it became commercially available; L (+) lactic acid was formed by natural products such as cheese, yoghurt, sourdough, meat product and wine. The animal and human bodies also produce significant amounts of L (+) lactic acid during daily activities, such as waling and running. It is present in blood, kidneys, muscles, hair and skin. Nowadays, L (+) lactic acid is produced on a large scale by the fermentation of sugar. Besides the well known applications of L (+) lactic acid and lactates in cosmetics products, it is also applied in pharmaceutical products and in many food products. Natural lactic acid and lactates have been used for many years in a wide variety of cosmetic products. The major applications are as moisturizer and AHA (alpha hydroxyl acid) in skin care product and as a pH regulator in hair care products and toiletries.